Book Review: The Seven Principles for Making Marriage Work - Neal Van Zutphen (Journal of Financial Therapy, 2016)
The Seven Principles for Making Marriage Work is a relationship self-help book for individuals who have chosen to be in a relationship and also those who aspire to be in a relationship. This book has proven helpful to those in relationship counseling and coaching professions as well. The book covers why marriages work and why they fail. The seven principles provide the roadmap to ways of being together and methods for resolving conflicts and solving problems, including money.
Keywords: book review; marriage; money; financial therapy